Blind recognition of binary BCH codes based on Euclidean algorithm. Issue 21 (1st September 2020) - Yu, Ming; Zheng, Feifei; Ma, Junwei; Zhang, Jingying
Abstract : A novel method based on Euclidean algorithm is proposed to solve the problem of blind recognition of binary Bose–Chaudhuri–Hocquenghem (BCH) codes in non‐cooperative applications. By carrying out iterative Euclidean divisions on the demodulator output bit‐stream, the proposed method can determine the codeword length and generator polynomial of unknown BCH code. The computational complexity is derived as O ( n 3 ). Simulation results show the efficiency of the proposed method.